Створення асистентів на базі штучного інтелекту - Талах, В. О. (ХНУРЕ, 2024)
The text explores the popular trend of creating AI assistants through generative artificial intelligence. It addresses challenges in updating neural network knowledge and introduces LangChain as a framework for assistant development. The process includes information retrieval, storage, search, and response generation. The example used for illustration involves developing an assistant for document search, providing insights into the overall development process and the versatility of LangChain.
Keywords: LangChain; AI; створення асистентів